Factors Affecting Catheter Contact in the Human Left Atrium and Their Impact on Ablation Efficacy. (14th October 2014) - ULLAH, WAQAS; HUNTER, ROSS J.; BAKER, VICTORIA; DHINOJA, MEHUL B.; SPORTON, SIMON; EARLEY, MARK J.; SCHILLING, RICHARD J.
Factors Influencing AF Ablation Efficacy Introduction Preclinical work suggests factors including catheter orientation and contact consistency during individual radiofrequency ablations influence lesion size. Our aim was to investigate factors affecting catheter contact in the left atrium (LA) and their effects on ablation. Methods and Results A total of 2, 298 8‐second static LA mapping points were studied in 30 patients undergoing ablation for AF (16 in AF, 14 sinus rhythm [SR], 18 remote robotic navigation [RRN] procedures) using a contact force (CF) sensing catheter. CF variability (CFV: difference between 20 Hz–sampled CF waveform mean peak and trough) increased with mean CF, Spearman's ρ = 0.6, P < 0.005. Catheter drift correlated weakly with CF (Pearson's correlation −0.06, P = 0.005). CFV was higher in SR than AF and with RRN (P < 0.001). In AF, there was less catheter drift for RRN than manual navigation points but the converse was true in SR. In 747 static 30 second LA ablations, the influence of contact parameters on ablation efficacy was compared by multivariate analysis of impedance drop during ablation: a lesser drop suggesting reduced efficacy. For a given force time integral (FTI), increased CFV (>5 g) and locational drift (>3.5 mm), perpendicular contact, SR and RRN usage were associated with a lesser impedance drop with ablation (P < 0.005 for each), suggesting reduced efficacy. Conclusions Beyond the FTI, the quality of catheter contact influences ablation efficacy, and clinical catheter contact is affected by multiple factors, including the atrial rhythm and catheter navigation mode. Maximal efficacy is provided by parallel contact with CFV ≤5 g, catheter drift ≤3.5 mm, and manual navigation.